Evaluation of the dead zone of radar stations - Maharramov, Roman; Hashimav, Elshan; Sabziev, Elkhan; Pashayev, Adalat (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
With the emergence of unmanned aerial vehicles, the assignments of combating them have also become significantly more relevant. Today, operational countermeasures against UAVs are of great importance. Modern UAVs are capable not only of conducting video reconnaissance in a certain area, but also of observing a specific object for a long time and striking it. After detecting and identifying UAVs by RLS, it is necessary to take measures to neutralize them. In the paper, a mathematical model of the evaluation of the dead zone of RLS working together for the effective detection of unmanned aerial vehicles was established and a comparison of the dead zone was made on concrete examples. The purpose of the research work is to solve the problem of effective placement of joint working RLS by mathematical methods for nonobserved remaining part of them had minimal volume and to select the necessary placement scheme.